Levels of cytokines (IL-1?, IL-2, IL-6, IL-8, TNF-?) and trace elements (Zn, Cu) in breast milk from mothers of preterm and term infants - Ustundag, B; Yilmaz, E; Dogan, Y; Akarsu, S; Canatan, H; Halifeoglu, I; Aygun, AD (Wiley, 2005)
It has been well documented that human milk contains several immunomodulator components which are important during infant period when the newborn's immune system is still under development. In this study, we aim at examining levels of cytokines, zinc (Zn), and copper (Cu) in milk from mothers of premature and mature infants, and comparing changes during lactation periods consequently. Milk was collected from total of 40 mothers ( group M: mothers of mature infants, n = 20; group PM: mothers of premature infants, n = 20) from four lactation stages: colostrum (0 - 7 days), transitional (7 - 14 days), mature milk (21 days), and mature milk (2nd month). Levels of cytokines (interleukin [IL]- 1 beta, IL-2, IL-6, IL-8, tumor necrosis factor- alpha [TNF-alpha]) were determined by chemiluminesence method, whereas atomic absorption spectrophotometer was used for the determination of Zn and Cu levels. Cytokine levels were determined to be high in colostrum and transient milk from mothers of full-term infants, whereas their levels were reduced drastically in the 21st day and the 2nd month milk (P < .01, P < .001). Similar trends were observed in milk from mothers of premature infants, but cytokine levels were significantly lower in colostrum compared to colostrum from mothers of mature infants (P < .01). The differences in cytokine levels were continuous in transient milk ( P < .05) and mature milk (21 days) (P < .05), whereas there was no statistically significant differences between milk from both groups of mothers in the 2nd month (P > .05). Zn levels in milk from mothers of premature infants were significantly lower compared to the ones from mothers of mature infants (P < .01) and these differences continued through the 2nd month. Although Cu levels were lower in milk from mothers of premature infants, there was no statistically significant difference except colostrum (P > .05). Our results clearly demonstrate that the level of immunomodulating agents such as cytokines and trace elements in milk from mothers of premature infants is less than the level of the same agents in milk from mothers of full-term infants. Although there are commercially available products for infant feeding, human milk is still the best natural nutrient for newborns. Therefore, when premature infants are breastfed, necessary precautions such as supplemantary diets must be considered for possible infections and risks related with immune system deficiency.
Keywords: Tumor-Necrosis-Factor; Interleukin-1-Beta; Expression; Lactation; Profile; Cells